HIV-specific CD8+ T lymphocytes in blood of long-term HIV-infected hemophilia patients - Daniel, Volker; Scherer, Sabine; Sadeghi, Mahmoud; Terness, Peter; Huth-Kühne, Angela; Opelz, Gerhard (BioResearch open access, 2013)
Hemophilia patients infected with human immunodeficiency virus (HIV) 30 years ago show increased proportions of activated CD8+DR+ blood lymphocytes. We hypothesized that this might indicate a cellular immune response directed against HIV and might be the reason for long-term clinical stability of these patients. CD8+ peripheral blood lymphocytes (PBL) reactive with six HIV and two cytomegalovirus (CMV) pentamers were determined in heparinized whole blood. Additional lymphocyte subsets as well as plasma cytokines and HIV-1 load were studied. Long-term HIV-infected hemophilia patients with (n=15) or without (n=33) currently detectable HIV-1 load in the plasma showed higher proportions of CD8+ lymphocytes reactive with HIV (p<0.001) and CMV pentamers (p=0.010) than healthy individuals. The cellular anti-HIV response tended to be stronger and more polyclonal in patients during periods of viral replication than in patients with retroviral quiescence (p=0.077). Anti-HIV CD8+ lymphocyte responses were strongest in patients with high counts of activated CD8+DR+ T (r=0.353; p=0.014) and low CD19+ B lymphocyte counts (r=−0.472; p=0.001). Patients with or without HIV-1 viral load showed normal Th1 and Th2 plasma cytokine levels and high plasma interleukin-6 (versus healthy controls, p=0.001) and tumor necrosis factor-α (p=0.020). Hemophilia patients who have been living with HIV for more than 30 years showed a polyclonal CD8+ T-cell response against HIV and CMV. This cellular antiviral immune response was strongest during periods of HIV-1 replication and remained detectable during periods of HIV-1 quiescence. We hypothesize that the consistent cellular anti-HIV-1 response in combination with highly active antiretroviral therapy ensures stability and survival of these chronically HIV-1-infected hemophilia patients.